2015
DOI: 10.12692/ijb/6.4.177-183
|View full text |Cite
|
Sign up to set email alerts
|

Enhance the allelopathic potential of two rice cultivar (Oryza sativa L.) by foliar application of salicylic acid under salinity stress

Abstract: In order to investigate the effect of salicylic acid under salinity stress as an allelopathy stimulator in rice cultivars a hydroponic and pot experiment was carried out in factorial arrangement. Rice cultivars (Tarom and Neda) were grown under different levels of salinity stress (0, 4dS/m and 8dS/m) until 5 leaf stage, also at the same time the salicylic acid was used as foliar (0, 1% and 2%). The root exudates were collected and used as a growth bio-inhibitor in barnayardgrass pot culture. The highest inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Li et al (2010) observed inhibited root growth, damaged seed cell membrane systems for mitochondria and chloroplasts, increased cell permeability, and consequently reduced crop growth rates by allelochemicals from of seedlings of M. pruriens and other crop species. Esmaeili and Heidarzade (2015) indicated that rice root exudates recorded the greatest inhibitory effects on chlorophyll, leaf area, root growth, and nitrogen content. Hooper et al (2015) reported root exudates of D. uncinatum inhibited weed growth.…”
Section: Effects Of Crop Root Leachates On Growth and Development Of Weedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2010) observed inhibited root growth, damaged seed cell membrane systems for mitochondria and chloroplasts, increased cell permeability, and consequently reduced crop growth rates by allelochemicals from of seedlings of M. pruriens and other crop species. Esmaeili and Heidarzade (2015) indicated that rice root exudates recorded the greatest inhibitory effects on chlorophyll, leaf area, root growth, and nitrogen content. Hooper et al (2015) reported root exudates of D. uncinatum inhibited weed growth.…”
Section: Effects Of Crop Root Leachates On Growth and Development Of Weedsmentioning
confidence: 99%
“…Inhibitory effects on germination and establishment of crops and weeds caused by crop residues have been reported (Zohaib et al, 2016;Ashraf et al, 2017). Effects on foliar enzyme activity, protein synthesis, photosynthesis, respiration, cell division and enlargement were observed by several researchers (Nishida et al, 2005;Cai & Mu, 2012;Esmaeili & Heidarzade, 2015), resulting in significant reductions in crop yields.…”
Section: Introductionmentioning
confidence: 97%